Destination brand identity: challenges, opportunities, and future research agenda - Manuel Escobar-Farfán; Amparo Cervera-Taulet; Walesska Schlesinger (Cogent Social Sciences)
Destination brand identity has become a crucial topic in tourism research, garnering considerable significance recently. This study aims to provide a scholarly contribution by conducting a bibliometric mapping analysis, specifically focusing on identifying areas that will significantly impact future research. The research uses SciMAT software to structure various topics into clusters based on their similarities and scientifically map them. The data sample comprises 295 papers published in the SCOPUS database between 1995 and 2022. The findings show the evolutionary structure of pertinent domains. The analysis identified eight main themes and proposed a research agenda to guide future lines of research: (a) tourist destination, (b) communications and digital technologies, (c) co-creation; (d) place branding, (e) cultural identity, (f) sustainable destination, (g) dimensionality, and (h) destination satisfaction. This article is a pioneering document in mapping this field of research, as it identifies relevant areas and sub-areas for current and future research. As a result, this article should be considered a guide for tourism and hospitality researchers.